Research of exhaust emissions by chainsaws with the use of a portable emission measurement system. Issue 3 (2nd September 2019) - Dimou, Vasiliki; Kantartzis, Apostolos; Malesios, Chrisovalantis; Kasampalis, Emmanouil
ABSTRACT: Anthropogenic activities in the environment have an impact on climate change. Among these activities is the use of the chainsaw which plays an important role by releasing greenhouse gas emissions in the atmosphere. Hence, the need for research on improved logging operations is of importance. The present study compares carbon monoxide (CΟ) and nitrogen dioxide (NO2 ) emissions generated by the engines of one catalytic chainsaw and two conventional chainsaws, of which one is professional and the other amateur. Measurements were carried out under three functional modes (infrequent accelerator use, use of quality oils, use of clean filters). Measurements that were conducted under normal conditions were named "witness measurements" and were used for future comparisons. Additionally, a set of measurements for CΟ and ΝΟ2 emissions was collected under different operation modes for all three types of saws (frequent accelerator use, use of low-quality oils, use of impure filters). Data collection was carried out in real conditions using a portable gas detector. Average concentration values of CΟ and ΝΟ2 under normal conditions for all three types of chainsaws found in the air of the operator's breathing zone were 88.32 ppm and 0.07 ppm, respectively. Results show that CO concentrations exceed the permissible exposure limit (50 ppm), whereas CO concentrations in excess of the short-term exposure limit (300 ppm) were only found in the case of the amateur chainsaw operated with low-quality oils. These results are of use towards efforts to reduce the CO and NO2 to the atmosphere.